Morphophonemie Relations in Kurdish Language - Mosa, Abdulwahab X. (Humanities Journal of University of Zakho, 2014)
The current study deals with the morphophoneme in the Kurdish language. It analyses the morphemes that have morphophoneme relation. Accordingly the research.divided into two section . section one deals with phonological and morphological concepts and the total relationship between them . It also includes the concept of morphophoneme and the rules that are relevant to morphology . Section tow is about the relationship of morpheme with some linguistic phenomena:these are 1- The relationship of Morphophoneme with the Phoneme. 2- The relationship of Morphophoneme with the Morpheme. 3- The relationship of Morphophoneme with the Allomorph. 4- The relationship of Morphophoneme with the Stress .